Per una "traditio" dell’opera di Franco Scaldati: Totò e Vicé, Assassina e Ombre folli secondo Randisi-Vetrano - Lipani, Domenico Giuseppe (Mimesis Journal, 2020)
This paper analyses the relationship between Franco Scaldati’s drama and the staging of his work made by Enzo Vetrano and Stefano Randisi. Totò e Vicè, Assassina and Ombre folli, staged by Diablogues, are three examples of how actor’s dramaturgy can interact with author’s writing, within common aesthetics, showing the possibilities for a “popular-experimental theatre”.